Mixed Use Building Kota Surabaya dengan Arsitektur Biophilic - Della Anastasya Dewi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
A Mixed Use Building project in downtown Surabaya is the basis of this design. The project is located on Menanggal Wisata street in Surabaya, which is in the area of Kodim Brawijaya and very strategic. To overcome the phenomenon, the designer should think about how to maximize the land function (in the middle of the city and dense environment) and organize the circulation system. because the multifunctional building project to be built should be able to carry out various functions in one space. Residential, coworking, and shopping center functions are all part of the building. The biophilic concept, which means applying natural elements both physically and non-physically to the inside and outside of the designed building, is a common concept in Mixed Use building design. The construction is a multifunctional building with three floors of shopping center and eight floors of apartment units. The building period consists of two main basic forms, which are connected by a connecting mass for the apartment spaces.